What Works in Offender Compliance - Ugwudike, Pamela. author. aut Link
XV, 365 p.
Keywords: This comprehensive edited collection draws together the latest international literature on offender compliance during penal supervision and after court orders expire. Outlining emerging developments in compliance research, theory, policy and practice, this book considers a wide range of offenders including women and young people.